The Objectivity of Nonexistent in the View of Mu'tazila and an Analysis of Received Criticisms on it - Aflatoon Sadeghi (Comparative Theology)
Mu'tazila put forward the theory of the objectivity of nonexistent to prove God's eternal knowledge of possible beings before creation. The criticisms of Ash'arites and Islamic philosophers are the eternity of the world, denying the contradiction and its ineffectiveness in proving God's eternal knowledge of creatures. According to the semantics of objectivity and non-existent, there is no criticism in Mu'tazila's point of view of the denying of contradiction and the eternity of the world. In this theory, objectivity means a constant that can be reported. The non-existent in this theory is something that does not exist on the outside. Therefore, objectivity of non-existent is the stability of things that do not exist outside, but exist in God's eternal knowledge, and this does not mean the eternality of objective beings. Similarly, stability is external existence and is not in contradiction with the negation of external existence. Therefore, the principle of this opinion is rationally acceptable. On the other hand, the requirement of this theory is the contradiction between existence and essence, mental existence and the belonging of counterfeit to the existence. This study examines this theory and its criticisms using a descriptive-analytical method. Keywords: Mu'tazila, Objectivity, Nonexistent, Eternity of the World, Eternal Knowledge. IntroductionThe attribute of divine knowledge appears in the theological and even philosophical works of Muslim thinkers more than other attributes. There are more than 350 verses of this attribute in the Holy Qur'an. In the theological, philosophical, and mystical fields, in the discussion of God's knowledge, God's knowledge of other beings before creation has been a complicated issue. How can things that do not have a reality become known to divine knowledge? One of the opinions put forward in this context and attributed to the Mu'tazila is the theory of objectivity of nonexistent. Ash'ari and Imamiyyah theologians, Ibn Sina, Suhrawardi, Mulla Sadra and other Islamic philosophers have proposed and criticized this theory in their works. In addition, in recent years, some works have been published in this field. The importance of examining this theory in Islamic theology goes back to solving the important issue of divine knowledge of beings before creation. The research questions of this study are: 1) What does Mu'tazila mean by objectivity, nonexistent, and the objectivity of nonexistent? 2) What is the effectiveness of the objectivity of nonexistent theory in proving God's eternal knowledge? 3) What is the effectiveness of incoming criticisms? This research hypothesizes that, with a thorough analysis, it can be said that these criticisms do not apply to the group that emphasizes the originality of reason. Materials and MethodsBased on the methodology of religious and scientific studies, in this research, the topic has been discussed first. Then, since there are many theoretical differences in the definition of fundamental concepts, an effort has been made to clearly express the definition of these concepts in this theory using the semantic method. Then, according to the descriptive-analytical method, the description of those concepts, the principle of the theory, and the received criticisms have been presented. Then, with a final analysis, it has been shown that the effectiveness of this theory can be determined by the semantics of its keywords in the works of Mu'tazila. Considering the centrality of analysis of the main concepts in data collection, this research relies on the library method and the main texts. Research FindingsThe theory of eternal Shiism from Mu'tazila’s point of view means that things are fixed in divine knowledge that do not exist outside of eternity. Therefore, God's knowledge of creatures before creation is justifiable, without any change in His essence. Their critics claim that the Mu'tazila have placed something called stability between the two opposites of existence and non-existence, which is against reason. On the other hand, theologians emphasize that this theory will lead to the acceptance of the eternity of the world, which is not acceptable from a religious point of view. In addition, it does not have the necessary efficiency to realize its goal, which is to prove the eternal knowledge of God before creation. According to the works of Mu'tazila, it can be said that objectivity in this theory has a fixed meaning that can be reported. On the other hand, when the Mu'tazila talk about non-existence and non-existence objects, they not only mean external non-existence as opposed to external existence and being but also both external non-existence and non-existence. Therefore, one of the examples of non-existence in this theory is a known issue that does not have an external real existence, and non-existence is the stability of things that do not exist outside the object, but exist in God's eternal knowledge. This does not mean the eternality of objective beings. Similarly, what inferred from Mu'tazila's statements is that stability is both an external existence and not in contradiction with the negation of external existence. Therefore, according to the semantics of the object and the non-existence in the works of the Mu'tazila, the criticism of the contradiction and the eternity of the world will be rejected. By referring to the works of Mu'tazila and explaining the meaning of the object and the non-existence, the criticisms are rejected, and the effectiveness of this point of view in proving its goal, which is to prove God's eternal knowledge of creatures, is accepted based on its foundations. Discussion of Results and ConclusionsIn spite of minor differences, the theory of objectivity of nonexistent to solve the problem of divine knowledge is attributed to Mu'tazila. Mu'tazila believe that things are fixed in divine knowledge before they are created, and based on them, beings are realized outside. They have no difference in correspondence with external objects after creation. Therefore, objects are non-existent before their creation, but they exist as objects in divine knowledge. This theory has been criticized and rejected by Ash'ari theologians and Islamic philosophers. According to the Mu'tazila's meaning of objectivity, it means something that is fixed in some way and can be reported, and the meaning of non-existent means something that does not exist outside. Based on the meaning that the Mu'tazila define as knowledge, which is a belief that takes place in the soul of a person, and the meaning they have of the term "fixed" in the sense of external existence, the theory of objectivity of nonexistent can be justified in itself. This theory is effectively based on principles such as the contradiction between existence and essence, mental existence, and the belonging creation to existence, which are philosophical principles. Of course, in terms of the principle of essence, this theory is not efficient because it leads to the eternity of the possible beings or the multiplicity of divine nature.